2010
DOI: 10.1203/00006450-201011001-00072
|View full text |Cite
|
Sign up to set email alerts
|

72 Parental Satisfaction Concerning Their Child's Hospital Care: A Questionnaire Survey

Abstract: Oral Abstracts 39 4. Health economic modelling of the costs and effectiveness of CCTH models. Results:The international evidence base on costs and effectiveness of CCTH remains weak. Three main models of CCTH are evident, with different organisational and delivery features and costs. Conclusions:Children with complex, long-term care needs, as well as children with acute conditions that will resolve can be and are cared for safely closer to home. However, barriers and facilitators to further development of CCTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…They observed that the key factors contributing to parental satisfaction were the adequacy of care, effective pain management, parental involvement in care, establishment of trust, and staff attitudes. 14 Wun et al conducted a study that employed both qualitative and quantitative methods, revealing that the most significant factors in doctor selection were the proximity of the clinic's location and the fees and charges of the hospital 15 which are almost identical to this present study.…”
Section: Discussionsupporting
confidence: 73%
“…They observed that the key factors contributing to parental satisfaction were the adequacy of care, effective pain management, parental involvement in care, establishment of trust, and staff attitudes. 14 Wun et al conducted a study that employed both qualitative and quantitative methods, revealing that the most significant factors in doctor selection were the proximity of the clinic's location and the fees and charges of the hospital 15 which are almost identical to this present study.…”
Section: Discussionsupporting
confidence: 73%
“…Like in the studies conducted by other authors, the age and sex of parents were not determinants of the satisfaction with nursing care [16,33,34,39]. However, there are no unambiguous reports in this area [10,12,40]. The diversity of outcomes in research reports and our study results may be influenced by the choice of a research tool, as well as the family model (patriarchal/matriarchal/partnership) or cultural/national influences.…”
Section: Discussionmentioning
confidence: 84%